The evolution of time use approaches for understanding activities of daily living in a public health context - Josephine Y. Chau; Sjaan R. Gomersall; Hidde P. van der Ploeg; Karen Milton (BMC, 2019)
Abstract This Supplement aims to raise awareness and knowledge of how time use surveys may be applied to studying health behaviours such as physical activity, sedentary behaviour, and eating. This commentary provides an overview and discussion of the papers in this Supplement about time use and health research, and considers possible future directions for the field.